Makna Pesan Fashion sebagai Komunikasi Non Verbal pada Film "Mrs. Harris Goes to Paris" - Nabila Muthia Khansa; Ani Yuningsih (Bandung Conference Series: Journalism, 2024)
Abstract. Movies as part of mass communication media can influence its audience widely through a story idea and characters. Fashion as a non-verbal communication is seen as everyone's tool to reflect who the wearer is, but in today's reality, the concept of fashion as a non-verbal communication has begun to shift and is misused as if everyone has the right to judge someone through clothing. Mrs. Harris Goes to Paris is a film that examines fashion and discrimination of significant social class differences in the 1950s. Therefore, researchers want to reveal and interpret what meanings are contained in the movie Mrs. Harris Goes to Paris. This research uses a qualitative method, with Gadamer's Hermeneutics approach, which is processed through Gadamer's four main aspects (1) Historical Aspect, (2) Prejudice Aspect, (3) Hermeneutic Circle Aspect, (4) Application Aspect. The results of this study interpret the meaning of fashion in the film as identity, social class, culture, discrimination and the phenomenon of consumerism which is also a criticism in the film that targets Mrs. Harris' character who seems to emphasize the importance of luxury goods for an ideal happiness. Abstrak. Film sebagai media massa dapat mempengaruhi khalayaknya secara luas melalui sebuah ide cerita dan karakter. Fashion sebagai komunikasi non verbal dipandang sebagai alat setiap orang untuk mencerminkan siapa diri pemakainya, namun realitas saat ini, konsep tersebut mulai beralih geser dan disalah gunakan, seolah setiap orang berhak menghakimi yang lainnya melalui pakaian. Film Mrs Harris Goes to Paris merupakan film yang mengkaji mengenai fashion dan diskriminasi perbedaan kelas sosial yang signifikan di tahun 1950. Maka dari itu, peneliti ingin mengungkap dan menginterpretasikan makna apa saja yang terdapat di film Mrs. Harris Goes to Paris. Penelitian ini menggunakan metode kualitatif, dengan pendekatan Hermeneutika Gadamer, yang diproses melalui empat aspek pokok Gadamer (1) Aspek Historis, (2) Aspek Prasangka, (3) Aspek Lingkaran Hermeneutika, (4) Aspek Penerapan. Hasil dari penelitian ini menginterpretasikan makna fashion di film sebagai identitias, kelas sosial, budaya, diskriminasi dan fenomena konsumerisme yang sekaligus menjadi kritik dalam film yang membidik karakter Mrs. Harris yang seolah menekankan pentingnya barang mewah untuk sebuah kebahagian yang ideal.